Aspectos financieros en las empresas industriales de Boyacá. (2020)
In the realization of this article, the objective is aimed at proposing some reflections on the incidence of finances for decision-making in small and medium-sized industrial companies in the geographic area under investigation, the department of Boyacá. Based on the review and analysis of research works conducted by different entities that provide information regarding the topic, the financial actions of the companies from Boyacá is understood, thus it is possible to contribute to set clear objectives with a long-term scope, such as maximizing their value, optimizing capital and operating financing needs. Among the works found, it is detected and analyzed that SMEs in this region have been managed with relative ineffectiveness in the financial aspect, since the absence of professional criteria is relevant and failing that, ancestral and/or traditional family knowledge emerge forgetting about the importance of analysis in accounting, economic and financial aspects; in such a way that there is an incidence in the management of the same business organizations, which is reflected in aspects such as competitiveness and productivity.